Economic/Environmental Optimal Power Flow Using a Multiobjective Convex Formulation - Yamaguti, Lucas do Carmo [UNESP]; Home-Ortiz, Juan Manuel [UNESP]; Pourakbari-Kasmaei, Mahdi; Mantovani, José Roberto Sanches [UNESP] (MDPI, 2023)
This paper addresses the problem of economic/environmental optimal power flow with a multiobjective formulation using a second-order conic programming (SOCP) optimization model. This problem formulation considers renewable energy sources (RES), fossil-fuel-based power generation units, and voltage control. The proposed SOCP model is a stochastic scenario-based approach to deal with RES and load behavior uncertainties. An ε-constrained algorithm is used to handle the following three objective functions: (1) the costs of power generation, (2) active power losses in the branches, and (3) the emission of pollutant gases produced by fossil-fuel-based power generation units. For comparative purposes, the SOCP model is also presented using a linearized formulation, and numerical results are presented using a 118-bus system. The results confirm that changing the energy matrices directly affects the cost of objective functions. Additionally, using a linearized SOCP model significantly reduces reactive power violation in the generation units when compared to the nonlinearized SOCP model, but also increases the computational time consumed.
Keywords: emission pollutant gasses; multiobjective optimization; optimal power flow; renewable energy sources; second-order conic programming; ε-constrained algorithm